The twelve prophets ; v. 1 - Craigie, Peter Campbell, 1938-1988 (Edinburgh, Scotland Saint Andrew, 1984)
Contents : v. 1 : Hosea, Joel, Amos, Obadiah And Jonah. Includes bibliographical references.
Keywords: Bible. O.T. Minor Prophets -- commentaries